An impact study of the economic partnership agreements in the six ACP Regions - Fontagné, Lionel; Laborde Debucquet, David; Mitaritonna, Cristina (Oxford University Press, 2011)
This article provides a detailed analysis of the trade-related aspects of economic partnership agreement (EPA) negotiations for the six Africa-Caribbean-Pacific (ACP) negotiation groups including ECOWAS, CEMAC+, COMESA, SADC, CARIFORUM and Pacific. We use a partial equilibrium model—focusing on the demand side—at the HS6 level (covering 5,113 HS6 products). Two lists of sensitive products are constructed: focusing on the agricultural sectors and tariff revenue preservation. For the European Union (EU), EPAs must translate into 90% fully liberalised bilateral trade to be World Trade Organisation compatible. We use this criterion to simulate EPAs for each negotiating regional block. ACP exports to the EU are forecast to be 10% higher with EPAs, than under the generalised system of preference ‘Everything But Arms' option. ACP countries, especially African ones, are forecast to lose an average of 71% of tariff revenues on EU imports in the long run. Imports from other regions of the world will continue to provide tariff revenues. Thus, if we compute tariff revenue losses on total ACP imports, losses are only 25% on average over the long run and as low as 19% if the product lists are optimised. The final impact depends on the importance of tariffs in government revenue and on potential compensatory effects. However, this long-term and less visible effect will depend mainly on the capacity of each ACP country to reorganise its fiscal base.